Indigenous Land-Based Approaches to Well-Being: The Amisk (Beaver) Harvesting Program in Subarctic Ontario, Canada - Fatima Ahmed; Eric Liberda; Andrew Solomon; Roger Davey; Bernard Sutherland; Leonard Tsuji (International Journal of Environmental Research and Public Health, 2022)
The act of decolonizing knowledge systems involves recovering and renewing traditional, non-commodified cultural patterns, such as the sustenance of intergenerational relationships and traditional practices. A decline in beaver harvesting, which was once an integral part of the Omushkego Cree culture, has resulted in an overabundance of beavers and dams, which has negatively affected communities by increasing the local flooding events and impacting the water quality. The aim of the Amisk (beaver) program was to reconnect the Elders and youth to revitalize traditional on-the-land activities and, in the present case, beaver harvesting and associated activities within the community. The program and evaluation were built using a two-eyed seeing (Etuaptmumk) and community-based participatory research approach. Salivary cortisol, a biomedical measure of stress, was collected before and after participation in the program. Photovoice, along with semi-directed interviews, were employed to identify the key elements of well-being from a First Nations’ perspective. For the beaver harvesting activities, the changes observed in the cortisol concentrations were not statistically significant (p = 0.094). However, the act of beaver dam removal was associated with a statistically significant increase in the post-participation cortisol concentration (p = 0.021). It was noteworthy that increased stress during the removal of the beaver dams–as indicated by the elevated post-activity cortisol levels–were not reflected in a decrease in the qualitative measures (semi-directed interviews and photovoice) of well-being from an Indigenous perspective. In fact, there was a noted increase in the subjective well-being of the participants, which highlights the importance of multiple perspectives when assessing well-being, especially in Indigenous peoples. However, the cortisol findings of the present pilot project need to be interpreted with caution, due to the limited sample sizes.